Comparison the Effect of Extra Corporeal Shockwave Therapy with Low Dosage Versus High Dosage in Treatment of the Patients with Lateral Epicondylitis - Taheri, Parisa (Adv Biomed Res, 2017)
BACKGROUND: One of the most common reasons of elbow and forearm pain is lateral epicondylitis diagnosed based on clinical examination. The extracorporeal shock wave therapy is applied for less invasive treatments with different dosages. This study aimed to investigate the effects of high- and low-dose ESW in treating the lateral epicondylitis. MATERIALS AND METHODS: This clinical trial was done in Al Zahra medical center on 40 patients who were selected randomly and divided into two groups. After VAS, the first group was treated by Duolith SD1 shock wave, energy of 0.25 mj/mm(2), 1000 shocks; the second was treated by focus with the energy of 0.10 mj/mm(2), 1000 shocks per session for 15 minutes with weekly intervals in three sessions. The patients were also treated with drugs (NSAIDs) and the visual analog scale (VAS) was reassessed 1 week after the last session and 12 weeks after finishing the treatment. RESULTS: The mean of pain intensity during study was decreased in the two groups but reduction of pain intensity in the low-dose groups was higher than the high-dose groups (P = 0.001). Changes in other parameters including wrist extension test, middle finger extension test and PG was also similar. CONCLUSION: Extra corporeal shockwave therapy can be effective in treating lateral epicondylitis, but its effects usually appear in after 2 or 3 months and using the low dose of this treating method has more desirable therapeutic effects.